2013
DOI: 10.1130/l260.1
|View full text |Cite
|
Sign up to set email alerts
|

Late-stage foreland growth of China’s largest orogens (Qinling, Tibet): Evidence from the Hannan-Micang crystalline massifs and the northern Sichuan Basin, central China

Abstract: This paper addresses the timing of fi nal foreland growth of China's largest orogens: the Mesozoic Qin Mountains (Qinling) and the Cenozoic Tibetan Plateau. In particular, we ask when the front of the Qinling orogen fold-thrust belt was emplaced, and when the northern Sichuan Basin was affected by the eastward growth of the Tibetan Plateau. We employ zircon and apatite fi ssion-track and (U-Th)/He dating in the Proterozoic crystalline rocks of the Hannan-Micang massifs and the sedimentary rocks of the northern… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
63
0
5

Year Published

2014
2014
2022
2022

Publication Types

Select...
7

Relationship

3
4

Authors

Journals

citations
Cited by 55 publications
(70 citation statements)
references
References 65 publications
2
63
0
5
Order By: Relevance
“…2; Chen et al, 2010;Dong et al, 2011a;Hu et al, 2012;Meng et al, 2007;Meng and Zhang, 2000;Li et al, 2007;Ratschbacher et al, 2003;Shi et al, 2012Shi et al, , 2013Wang et al, 2011a;Yin andNie, 1993, 1996;Zhang et al, 2001Zhang et al, , 2010. For the intracontinental deformation, various fission-track and U-Th/He thermochronological investigations of the apatite and zircon have indicated that the Qinling Orogen experienced an intricate pattern of postorogenic uplift and exhumation during the Mesozoic-Cenozoic (Enkelmann et al, 2006;Hu et al, 2006aHu et al, , 2012Li et al, 2010a;Liu et al, 2009Liu et al, , 2013Shen et al, 2007;Tian et al, 2010;Wan et al, 2000Wan et al, , 2005Wang et al, 2011b;Xu et al, 2005Xu et al, , 2010Yang et al, 2013;Yin et al, 2001). The southern Qinling orogen has been uplifted since the Triassic-Jurassic Shen et al, 2007;Xu et al, 2010;Yang et al, 2013), but the northern Qinling Orogen uplifted only since the Cenozoic (Enkelmann et al, 2006;Hu et al, 2006a;Liu et al, 2013), and the rapid cooling documented in the southwestern Qinling Orogen started during the late Miocene (Enkelmann et al, 2006).…”
Section: Introductionmentioning
confidence: 96%
See 2 more Smart Citations
“…2; Chen et al, 2010;Dong et al, 2011a;Hu et al, 2012;Meng et al, 2007;Meng and Zhang, 2000;Li et al, 2007;Ratschbacher et al, 2003;Shi et al, 2012Shi et al, , 2013Wang et al, 2011a;Yin andNie, 1993, 1996;Zhang et al, 2001Zhang et al, , 2010. For the intracontinental deformation, various fission-track and U-Th/He thermochronological investigations of the apatite and zircon have indicated that the Qinling Orogen experienced an intricate pattern of postorogenic uplift and exhumation during the Mesozoic-Cenozoic (Enkelmann et al, 2006;Hu et al, 2006aHu et al, , 2012Li et al, 2010a;Liu et al, 2009Liu et al, , 2013Shen et al, 2007;Tian et al, 2010;Wan et al, 2000Wan et al, , 2005Wang et al, 2011b;Xu et al, 2005Xu et al, , 2010Yang et al, 2013;Yin et al, 2001). The southern Qinling orogen has been uplifted since the Triassic-Jurassic Shen et al, 2007;Xu et al, 2010;Yang et al, 2013), but the northern Qinling Orogen uplifted only since the Cenozoic (Enkelmann et al, 2006;Hu et al, 2006a;Liu et al, 2013), and the rapid cooling documented in the southwestern Qinling Orogen started during the late Miocene (Enkelmann et al, 2006).…”
Section: Introductionmentioning
confidence: 96%
“…For the intracontinental deformation, various fission-track and U-Th/He thermochronological investigations of the apatite and zircon have indicated that the Qinling Orogen experienced an intricate pattern of postorogenic uplift and exhumation during the Mesozoic-Cenozoic (Enkelmann et al, 2006;Hu et al, 2006aHu et al, , 2012Li et al, 2010a;Liu et al, 2009Liu et al, , 2013Shen et al, 2007;Tian et al, 2010;Wan et al, 2000Wan et al, , 2005Wang et al, 2011b;Xu et al, 2005Xu et al, , 2010Yang et al, 2013;Yin et al, 2001). The southern Qinling orogen has been uplifted since the Triassic-Jurassic Shen et al, 2007;Xu et al, 2010;Yang et al, 2013), but the northern Qinling Orogen uplifted only since the Cenozoic (Enkelmann et al, 2006;Hu et al, 2006a;Liu et al, 2013), and the rapid cooling documented in the southwestern Qinling Orogen started during the late Miocene (Enkelmann et al, 2006). The variable timings of uplift and exhumation at different locations in the Qinling Orogen represent differences in the pattern and timing of tectonism not only from south to north (Hu et al, 2006a;Liu et al, 2013) but also from east to west (Enkelmann et al, 2006).…”
Section: Introductionmentioning
confidence: 96%
See 1 more Smart Citation
“…The orogenic collapse resulted in relatively minor and continuous exhumation and erosion of the orogen although major transtensional and strike-slip faults were activated. This is also proved by some low-temperature geothermal ages (Hu et al, , 2006Dong et al, 2008;Liu et al, 2013;Yang et al, 2013;Heberer et al, 2014).…”
Section: Late Cretaceous To Paleogene Orogenic Collapsementioning
confidence: 63%
“…Meanwhile, within the orogen, the Lower Jurassic strata were overthrusted, and the foreland fold-thrust belt formed in front of the MBXF. Rapid exhumation of some sectors of the Qinling orogen and adjacent areas is also elucidated by thermochronological studies (Zheng et al, 2004;Hu et al, 2005;Shen et al, 2007;Chang et al, 2010;Yang et al, 2013).…”
Section: Late Jurassic To Early Cretaceous N-s Compressionmentioning
confidence: 97%